Profound Intellectual Disability and the Grammar of Baptism - O'Farrell, Kevin (Journal of disability & religion, 2019)
The author argues that how the personhood of those with profound intellectual disabilities is imagined often becomes a determining factor in whether those with disability are included in communities or whether their lives are affirmed. The author suggests that the grammar of the Christian practice of baptism is beneficial in communicating the full personhood of those with disability as well as their full inclusion in and gifting for the church-community. This task is performed through a reading of Luther's 1529 treatise "Concerning Rebaptism" with the author relating it directly to those with profound intellectual disabilities.